2018
DOI: 10.1016/j.jjcc.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Initial pathological responses of second-generation everolimus-eluting stents implantation in Japanese coronary arteries: Comparison with first-generation sirolimus-eluting stents

Abstract: Histopathological analysis showed advanced healing process in 2nd DES compared with 1st DES lesions. These results are consistent with clinical beneficial outcome of 2nd DES implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Meta-analysis studies confirmed a lower target-lesion revascularization and incidence of stent thrombosis with newer-generation devices as compared to 1st generation DES and BMS [26,27]. The safety profile of second generation DES was also confirmed by intravascular imaging [28], angioscopy and pathology studies confirming improved stent coverage by neoendothelium associated with less aggregates of red blood cells, less peri-strut fibrin deposition, and a lower inflammation score [28,29]. Further evolutions to improve the biocompatibility of implants included the development of antithrombotic polymers (so-called fluoropassivation [25]), bioresorbable polymers (which however do not seem to improve significantly patients outcomes [30]), and completely bioresorbable scaffolds (whose mechanical characteristics, particularly strut thickness however represented a limitation [13,31,32]).…”
Section: Stent Complications and Stent Pathology Among Different Device Generationsmentioning
confidence: 83%
“…Meta-analysis studies confirmed a lower target-lesion revascularization and incidence of stent thrombosis with newer-generation devices as compared to 1st generation DES and BMS [26,27]. The safety profile of second generation DES was also confirmed by intravascular imaging [28], angioscopy and pathology studies confirming improved stent coverage by neoendothelium associated with less aggregates of red blood cells, less peri-strut fibrin deposition, and a lower inflammation score [28,29]. Further evolutions to improve the biocompatibility of implants included the development of antithrombotic polymers (so-called fluoropassivation [25]), bioresorbable polymers (which however do not seem to improve significantly patients outcomes [30]), and completely bioresorbable scaffolds (whose mechanical characteristics, particularly strut thickness however represented a limitation [13,31,32]).…”
Section: Stent Complications and Stent Pathology Among Different Device Generationsmentioning
confidence: 83%
“…Recently, the second-generation DES, including Xience/Promus everolimus- eluting stent, which consists of a thin strut platform coated with durable fluorinated copolymer and everolimus, were be in widespread use. In several pathological studies 34 , 35 ) , the second-generation DES showed greater strut coverage with less inflammation, less fibrin deposition, and less late and very late stent thrombosis compared with the first-generation DES. In our present study, there were no differences in plasma neopterin levels between patients with cardiovascular events and those without them in the first-generation DES.…”
Section: Discussionmentioning
confidence: 98%
“…The surge in interest in “Everolimus-eluting stents” highlights a focus on this second-generation drug-eluting stent, utilizing everolimus, categorized as an immunosuppressive drug and belonging to the class of mTOR (mammalian target protein of rapamycin) inhibitors, to counteract vascular endothelial cell proliferation and reduce the risk of ISR ( 113 115 ). Everolimus-eluting stents offer diverse designs and materials, facilitating comparisons with other stent types in long-term prognosis studies ( 85 , 116 118 ).…”
Section: Discussionmentioning
confidence: 99%